Bibliometric Analysis of Bibliometric Analyses on Oral Health Literature (1999-2024): A Meta-Bibliometric Approach (Bangladesh Journal of Medical Science, 2024)
This meta-bibliometric analysis investigates the evolution and trends of bibliometric analyses on oral health research over the past two and a half decades, based on publications in PubMed from 1999 to 2024. The study reveals a notable increase in the volume of bibliometric analyses, with China emerging as the leading contributor, followed by Brazil, India, and Saudi Arabia. The analysis highlights a trend towards international collaboration, enhancing the breadth of research perspectives. Major research themes include endodontics, dental caries, and pediatric dentistry. Despite these advancements, the study identifies gaps, including the need for more inclusive and multilingual databases and bibliometric analysis software that simplifies data integration from multiple databases for more comprehensive analyses. Overall, this analysis presents the current landscape of bibliometric analyses on oral health research and offers the research community meaningful insights that can guide future bibliometric analyses and improve the quality and relevance of oral health research assessments. The increasing volume and diversity of research output reflect a maturing field with a global focus. In contrast, the need for methodological advancements and broader inclusivity in research outputs points to areas for future development.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 934-949